2023
DOI: 10.1002/anie.202300314
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Hole Transport Properties via Pyrrole Derivation for High‐Performance Perovskite Solar Cells

Abstract: Hole transport materials (HTMs) with high hole mobility, good band alignment and ease of fabrication are highly desirable for perovskite solar cells (PSCs). Here, we designed and synthesized novel organic HTMs, named T3, which can be synthesized in high yields with commercially available materials, featuring a substituted pyrrole core and triphenylamine peripheral arms. The capability of functionalization in the final synthetic step provides an efficient way to obtain a variety of T3‐based HTMs with tunable en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…In addition to these common groups, fluorines (F) with strong electronegativity, hydrophobic property, and high stability have also been introduced into the passivating materials to enhance the passivation effect. [8][9][10][11][12][13] For example, the F groups can directly interact with Pb 2 + defects to suppress interfacial recombination [14] or enhance the interaction between the additive molecule and the perovskite film for reducing defect densities of perovskite. [15] It has also been reported that the F groups can form a large molecular dipole within the passivator, providing a directional field for charge separations, [16] or form hydrogen bonds between the passivator and methylamine ion to inhibit ion migration in the perovskite film.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these common groups, fluorines (F) with strong electronegativity, hydrophobic property, and high stability have also been introduced into the passivating materials to enhance the passivation effect. [8][9][10][11][12][13] For example, the F groups can directly interact with Pb 2 + defects to suppress interfacial recombination [14] or enhance the interaction between the additive molecule and the perovskite film for reducing defect densities of perovskite. [15] It has also been reported that the F groups can form a large molecular dipole within the passivator, providing a directional field for charge separations, [16] or form hydrogen bonds between the passivator and methylamine ion to inhibit ion migration in the perovskite film.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 Therefore, when n is smaller, a device is closer to the ideal device, and the non-radiative coincidence is smaller. 30 After TTA modification, the ideality factor decreased from 1.79 to 1.24, indicating the reduced nonradiative recombination due to TTA. As revealed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…, Cu:NiO x with a thin layer of an organic polymer, PhNa-1T), that offer improved stability and interface properties. 108,109 These materials can potentially address the shortcomings of conventional HTL materials like PEDOT:PSS and PTAA, ultimately leading to more efficient and stable PSCs.…”
Section: Outlook and Challengesmentioning
confidence: 99%
“…Recent advances in HTL materials have led to the development of novel alternatives, such as inorganic materials (e.g., triphenylamine-containing pyrrole-based HTM T3) or hybrid organic-inorganic compounds (e.g., Cu:NiO x with a thin layer of an organic polymer, PhNa-1T), that offer improved stability and interface properties. 108,109 These materials can potentially address the shortcomings of conventional HTL materials like PEDOT:PSS and PTAA, ultimately leading to more efficient and stable PSCs.…”
Section: Existing Challengesmentioning
confidence: 99%